2020
DOI: 10.1002/cpt.1852
|View full text |Cite
|
Sign up to set email alerts
|

Response to Inhibition of Receptor‐Interacting Protein Kinase 1 (RIPK1) in Active Plaque Psoriasis: A Randomized Placebo‐Controlled Study

Abstract: Receptor‐interacting protein kinase 1 (RIPK1), a regulator of inflammation and cell death, is a potential therapeutic target in immune‐mediated inflammatory diseases (IMIDs). The objective of this phase IIa multicenter, randomized, double‐blind, placebo‐controlled study was to evaluate safety, tolerability pharmacokinetics, pharmacodynamics, and preliminary efficacy of GSK2982772, a RIPK1 inhibitor, in plaque‐type psoriasis. Psoriasis patients (N = 65) were randomized to 60 mg twice daily (b.i.d.) or three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 16 publications
(23 reference statements)
1
58
0
Order By: Relevance
“…Overall, the complexity of RIPK1’s role in skin inflammation suggests that caution should be taken when targeting RIPK1 in all hyperinflammatory disorders, or that rationally designed drugs targeting other cell death machinery may have merit [ 158 ]. Encouragingly, a recent Phase II clinical trial using RIPK1 inhibitor GSK2982772 in plaque-type psoriasis has shown therapeutic benefit but there is still a lack of data surrounding RIPK1 inhibitors and their long-term use in the clinic [ 163 , 164 ].…”
Section: Skin—psoriasis and Dermatitismentioning
confidence: 99%
“…Overall, the complexity of RIPK1’s role in skin inflammation suggests that caution should be taken when targeting RIPK1 in all hyperinflammatory disorders, or that rationally designed drugs targeting other cell death machinery may have merit [ 158 ]. Encouragingly, a recent Phase II clinical trial using RIPK1 inhibitor GSK2982772 in plaque-type psoriasis has shown therapeutic benefit but there is still a lack of data surrounding RIPK1 inhibitors and their long-term use in the clinic [ 163 , 164 ].…”
Section: Skin—psoriasis and Dermatitismentioning
confidence: 99%
“…While these showed some promise in phase II, these were returned to the research phase in late 2019 by their licensee GlaxoSmithKline [15]. At the time of writing, there are only three active clinical trials in progress: a phase I trial assessing the safety of a new RIPK1 inhibitor (GFH312), a phase II study utilising RIPK1-binding compound, SAR443122, in cutaneous lupus erythematosus patients and a phase I/II study utilising RIPK1 inhibitor GSK2982772 in psoriasis [16]. There are currently no 'first in human' trials of RIPK3-or MLKL-binding compounds listed on http://clinicaltrials.gov (accessed on 28 May 21).…”
Section: Introduction Necroptosis and Diseasementioning
confidence: 99%
“…Following completion of the initial phase II clinical trials with GSK′772 in ulcerative colitis, RA and psoriasis, phase Ib trials in psoriasis were reinitiated at a much higher dose (960 mg versus 60 mg daily) 181 . GSK′772 has continued to show an excellent safety profile in a phase IIa clinical trial in mild to moderate plaque psoriasis, but additional data may be needed to demonstrate efficacy in this indication 182 . DNL104 (Denali Therapeutics) was the first brainpenetrant RIPK1 inhibitor advanced into a phase Ia clinical trial; although this programme was later discontinued owing to limited post-dosing liver toxicity deemed unrelated to RIPK1 inhibition, this study demonstrated the safety of inhibiting RIPK1 in the CNS 183 .…”
Section: Clinical Trialsmentioning
confidence: 99%